A qualitative exploration of the therapeutic characteristics of the art of therapy: Perspectives on Ayres Sensory Integration - Beverley Margaret Williams; Jean Daly-Lynn (PLoS ONE, 2025)
Since Dr. Jean Ayres first ignited the spark that became Ayres Sensory Integration® others have followed, inspired by her legacy to continue her dedicated life’s work. This theoretical approach continues to evolve, yet its fundamental core principles remain true to Dr Ayres’s original ideal. Empowering practitioners to set the just right challenge, an inviting therapeutic relationship, and to entice engagement through play was conceptualized as the art of therapy. This qualitative phenomenological study explores the therapeutic characteristics of the art of therapy, emphasizing the just right challenge, the therapeutic relationship and the experience of flow from the occupational therapist’s viewpoint. Eight participants kept reflective journals and engaged in semi-structured interviews which were analyzed using reflective thematic analysis. Three overarching themes were developed; 1) “The Human Connection” exploring components of the therapeutic relationship; 2) “Setting the Scene” investigating how the just right challenge is set, including the preparation and external factors involved; 3) “Magic Happens! The Optimal Experience” exploring a sense of achievement, how flow feels and how it is learned. Participants shared their unique therapeutic observations and provided clear insight into their understanding of the art of therapy. The findings demonstrated that this concept is complex and multifaceted with learning enhanced through mentorship and hands-on experiences. This highlighted the significant implications for the education and ongoing mentoring of both practicing and new clinicians. This study provided novel insight into the field of occupational therapy using Ayres Sensory Integration® by developing a deeper understanding of therapists’ experiences of the art of therapy.